Palindromic Sequence-Targeted (PST) PCR, Version 2: An Advanced Method for High-Throughput Targeted Gene Characterization and Transposon Display - Kalendar, Ruslan; Shustov, Alexandr V.; Schulman, Alan H. (Frontiers in Plant Science, 2021)
Genome walking (GW), a strategy for capturing previously unsequenced DNA fragments that are in proximity to a known sequence tag, is currently predominantly based on PCR. Recently developed PCR-based methods allow for combining sequence-specific primers with designed capturing primers capable of annealing to unknown DNA targets, thereby offering the rapidity and effectiveness of PCR. This study presents a methodological improvement to the previously described GW technique known as Palindromic Sequence-Targeted PCR (PST-PCR). Like PST-PCR, this new method (called PST-PCR v.2) relies on targeting of capturing primers to palindromic sequences arbitrarily present in natural DNA templates. PST-PCR v.2 consists of two rounds of PCR. The first round uses a combination of one sequence-specific primer with one capturing primer. The second round uses a combination of a single (preferred) or two universal primers; one anneals to a 5’ tail attached to the sequence-specific primer and the other anneals to a different 5’ tail attached to the PST primer. The key advantage of PST-PCR v.2 is the convenience of using a single universal primer with invariable sequences in GW processes involving various templates. The entire procedure takes approximately 2–3 hours to produce the amplified PCR fragment, which contains a portion of a template flanked by the sequence-specific and capturing primers. PST-PCR v.2 is highly suitable for simultaneous work with multiple samples. For this reason, PST-PCR v.2 can be applied beyond the classical task of GW for studies in population genetics, in which PST-PCR v.2 is a preferred alternative to amplified fragment length polymorphism or next-generation sequencing. Furthermore, the conditions for PST-PCR v.2 are easier to optimize, as only one sequence-specific primer is used. This reduces non-specific RAPD-like amplification and formation of non-templated amplification. Importantly, akin to the previous version, PST-PCR v.2 is not sensitive to template DNA sequence complexity or quality. This study illustrates the utility of PST-PCR v.2 for transposon display, which is a method to characterize inter- or intra-specific variability related to transposon integration sites. The Ac transposon sequence in the maize genome was used as a sequence tag during the transposon display procedure to characterize the Ac integration sites.